Bioinformatics for Beginners :Genes, Genomes, Molecular Evolution, Databases and Analytical Tools - Supratim Choudhuri (Academic Press is an imprint of Elsevier, 2014)
Bioinformatics for Beginners provides a coherent and friendly treatment of bioinformatics for any student or scientist within biology who has not routinely performed bioinformatic analysis. The book discusses relevant principles needed to understand the theoretical underpinnings of bioinformatic analysis, and demonstrates with examples targeted analysis using freely available web-based software and publicly available databases. Eschewing non-essential information, the work focuses on principles and hands-on analysis and points to many further study options.